Leadership in Muhammadiyah: A Case Study of the Muhammadiyah Organisation in Kudus Regency - Saputra, Viant Anggi; Mas'ud, Fuad (Jurnal Manajemen Bisnis, 2023)
Muhammadiyah, the world's largest Islamic organisation, grows by preaching amar ma'ruf nahi mungkar and non-profit Islamic leadership programmes that empower communities. Islamic leadership differs from western leadership, which is frequently the mecca of organisations. The Kudus branch of Muhammadiyah has grown rapidly, as shown by its charities in different community areas. Methods of research The qualitative case study method collects data through interviews, observation, and documentation across time. The strategy was used to focus and deepen study on Muhammadiyah leadership in Kudus organisations. Results of research Muhammadiyah leaders understand leadership well. The success of Muhammadiyah's collective-collegial leadership in the Kudus region is attributed to its persistence in applying seven Islamic leadership principles: justice, amar ma'ruf nahi munkar, ihsan, wisdom, humility, service to the people, visionary, and deliberation.